Regional variation in lumbar spine surgery in Saskatchewan: a population-based analysis. (3rd June 2015) - Fourney, DR; Dalkilic, T; Barrett, P; Buwembo, J; Ekong, C; Groot, G
Abstract : Background: Unexplained significant variation may suggest a quality care problem in a health care system. The objective of this study was to determine the extent of variance in spine surgery Saskatchewan and determine possible causes. Methods: Provincial billing records for new spine surgery consultations from May 2011 through October 2012 were correlated with subsequent lumbar surgery. Two tertiary centers (TC1 and TC2) were compared with reference to the Health Region of origin of the patient. Wait times for surgery and utilization of spine pathway clinics was analyzed. Results: TC1 had significantly higher rates of spine fusion and lumbar spine surgery. The percentage of new referrals that went to surgery was 14.0% in TC1 and 11.8% in TC2 (p<0.0001, Z-Test). Population-based calculation of the rate of new referrals was 1581/482387 = 0.33% for TC1 vs. 970/601739 = 0.16% for TC2 (p<0.0001, Z-Test). Utilization of the spine pathway clinic was lower and wait times for surgery were longer in TC1. Conclusions: Causes of regional variation are unknown and likely multifactorial. In Saskatchewan, the most striking variance was that the rate of primary care referrals for lower back conditions in regions served by TC1 was double that for TC2. This could potentially be reduced through more regionally consistent utilization of the spine pathway.